PENGARUH METODE PEMBELAJARAN NHT (NUMBERED HEADS TOGETHER) TERHADAP HASIL BELAJAR PKN SISWA KELAS IV SD N WEDING 3 DEMAK - Intan Rahmawati; Andri Sukowilono (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2013)
In the learning process, one of which is learning civics, still commonly found in the teacher teaching only rely on conventional methods. With teachers rely on conventional methods, students become active in learning. It is an effect on student learning outcomes. Therefore, the learning activities teachers need to implement appropriate teaching strategies. Thus the researchers conducted studies using NHT (Numbered Heads Together). Goals to be achieved in this study was to determine the effect of cooperative learning NHT (Numbered Heads Together) on student learning outcomes.This research is a quantitative research (experimental). Subjects in this study were students of class IV SDN Weding 3 Demak the number of 32 students. In this study, the class is divided into two groups, namely the experimental class and control class groups, each group class consists of 16 students. Analysis of the difference using T-test analysis, this analysis is used to determine the effect of the application of the method NHT (Numbered Heads Together) on learning outcomes of students in the experimental class and control class.Results of the study conducted on control class and experimental class, showed the average value in the classroom posttest control of 67.75 and 74.75 for the experimental class. From the results of data analysis known that the t value of 2.115 and t table value of 2.04, so t count> t table then H0 is rejected. So it can be concluded that there is a difference in learning outcomes between experimental control class to class. From the difference in the results of the study can be said that there is the effect of applying the method NHT (Numbered Heads Together) against Civics learning outcomes of fourth grade students of SDN Weding 3 Demak. From the results of this study suggested that becomes an input to be able to apply the method NHT (Numbered Heads Together) well.